A Cross-Lingual Security Evaluation of Prompt Injection Defenses in Small Language Models - Fuziwara Filho, Pedro; Aguiar, Erikson J. de; Traina, Agma J. M. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg_estendido.2026.33794, 2026)
Although language models are increasingly deployed in multilingual settings, the literature offers limited insight into the robustness of optimization-based defenses trained in a single language. In this paper, we investigate whether, and in what ways, the language used to construct a prompt influences its effectiveness against prompt injection in small language models. We also examine a defensive strategy against prompt injection, called DefensiveTokens, which can generalize to languages not observed during training. Our findings show that DefensiveTokens provide a robust defense against prompt injection attacks in multilingual applications.